AB0469 Efficacy and safety of interleukin 6 inhibitors in rheumatoid arthritis: a systematic literature review. (12th June 2018) - Oton, T.; Loza, E.; Sanmarti, R.; Tornero Molina, J.
Abstract : Background: Interleukin 6 (IL-6) inhibitors constitute a therapeutic option for patients with rheumatoid arthritis (RA). Currently, apart from Tocilizumab (TCZ), we have data from other drugs targeting the IL-6 pathway. Objectives: To review published evidence on safety and efficacy of IL-6 inhibitors in RA. Methods: We performed sensitive systematic literature searches in Medline and Cochrane (up to October 2017), screened EULAR and American College of Rheumatology meeting-abstracts. An expert librarian designed the strategies that included Mesh and text word terms. The search was limited to human RA, adults and the English and Spanish language. The inclusion criteria were as follow: 1) RA patients on IL-6 Inhibitors including TCZ, sarilumab (SAR), olokizumab, sirukumab and clazakizumab; 2) Placebo and an active comparator were accepted as comparators; 3) Articles including typical efficacy and safety variables such as DAS-28, radiographic progression or the infections rate; 4) Only meta-analyses, systematic reviews and clinical trials were selected. Two reviewers screened the titles and abstracts of the retrieved articles independently. They also collected the data from the studies included by using ad hoc standard forms. All collection was double by article and independent. Subsequently, a secondary manual search of the bibliography of the articles that were finally included was performed. Evidence tables were produced. The quality was evaluated with the Oxford 2009 scale. Results: We included 64 articles of moderate-high quality, variable duration, between 12 and 108 weeks. These articles analysed more than 8000 patients with RA, most of them with established RA (although there are data on early RA), with high disease activity and severity criteria. More than a half of the studies are of TCZ. IL-6 inhibitors were effective both in the short and long term in terms of clinical remission, RA activity, radiographic progression, function, fatigue, bone metabolism, morning stiffness, pain, quality of life, or anaemia. They also decreased and even normalised CRP values in a rapid and sustained manner. The efficacy of blocking IL-6 has been seen in RA refractory to DMARD or anti-TNFα and in MTX-naïve patients, as well as in the intravenous and subcutaneous formulations (TCZ). TCZ and SAR are more effective than adalimumab in monotherapy. In general, no statistically significant differences were found between combined therapy and monotherapy. In terms of safety, the rate of adverse events increased over time and with the concomitant use of DMARDs. Infections and hypersensitivity reactions were the most frequent adverse events and infections the most frequent serious adverse events. IL-6 inhibitors were associated with a rapid and subsequently sustainable increase in serum lipid parameters, although this was not associated with a higher prevalence of cardiovascular events and related mortality, nor was it associated with neoplasms. Transaminase elevations were generally mild and without serious disorders. The incidence of gastrointestinal perforations was very low, and it was associated with a previous history of diverticulitis. Conclusions: IL-6 inhibitors are effective to control RA activity and symptoms and to prevent radiographic damage in different disease profiles, with an acceptable safety profile. Disclosure of Interest: None declared